2018
DOI: 10.3892/or.2018.6915
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‑induced galectin‑3 enhances RhoA function to activate the motility of tumor cells in non‑small cell lung cancer

Abstract: Galectin-3 plays crucial roles in tumor progression. However, in non-small cell lung cancer (NSCLC), it remains unclear whether the hypoxic tumor microenvironment enhances galectin-3-induced cell motility. We investigated galectin-3 expression in NSCLC cells under hypoxia, and the possible molecular mechanisms by which galectin-3 influences tumor aggressiveness. Galectin-3 levels in NSCLC cell lines under hypoxia were assessed using reverse transcription PCR and western blotting. To clarify the role of endogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
(46 reference statements)
1
10
0
Order By: Relevance
“…[47][48][49][50] Gal3 is one of the major active components of the low oxygen/ischemic environment. 51,52 We have shown significant up-regulation of Gal3 in the post-stroke rat brain. Furthermore, blocking of Gal3 with neutralizing antibody decreased the cerebral blood vessel density.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…[47][48][49][50] Gal3 is one of the major active components of the low oxygen/ischemic environment. 51,52 We have shown significant up-regulation of Gal3 in the post-stroke rat brain. Furthermore, blocking of Gal3 with neutralizing antibody decreased the cerebral blood vessel density.…”
Section: Introductionmentioning
confidence: 81%
“…There is an emerging body of evidence that Gal3 is upregulated under a hypoxic micro-environment due to vaso-occlusion or defective angiogenesis, particularly in solid tumors to enhance their survival, growth, and invasion. 5163 Gal3 is also associated with cognitive impairment and aging. 64 Despite these compelling data, the specific role of Gal3 in post-stroke brain has not been systematically elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Kataoka et al . [41] reported that hypoxia could increase the expression of Gal‐3 in NSCLC cells and thus contributes to metastasis. In esophageal cancer, Gal‐3 can promote cancer progression through activation of the AKT/ERK pathway [42], while Yao et al .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Gal-3 may directly promote cancer progression and metastasis through multiple pathways. Kataoka et al [41] reported that hypoxia could increase the expression of Gal-3 in NSCLC cells and thus contributes to metastasis. In esophageal cancer, Gal-3 can promote cancer progression through activation of the AKT/ERK pathway [42], while Yao et al [43] reported that, in pancreatic cancer, inhibition of Gal-3 blocked the AKT/FOXO3 signaling pathway and subsequently suppressed cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Cultivation of PANC-1 cells under the hypoxic/nutrient-deprived condition not only stimulates autophagy but modulates positively the Gal-3 expression. Gal-3 upregulation under hypoxic exposure has been reported for other tumors as breast (de Oliveira et al, 2015), thyroid (Zheng et al, 2017), and non-small-cell lung carcinoma (Kataoka et al, 2019). Previous results of our research group brought the upregulation of mRNA Gal-3 when PANC-1 cells undergone hypoxic incubation (da Silva Filho et al, 2020).…”
Section: Discussionmentioning
confidence: 90%